Estudo do efeito da reticulação por genipin em suportesbiocompatíveis de quitosana-PVA - Viviane Mota Bispo (2009)
The human integument, known as skin, is made up of distinct layers, joined to each other. Its main functions are to protect the underlying tissues, regulate body temperature, and uphold somatic nerve endings. This human organ is subject to several types of effort and injuries caused by physical and chemical agents. By its importance, the skin has been the subject of many studies aimed at understanding their properties and produce materials that improve and speed its healing process. The world market is growing due the demand for biomaterials to treat epithelial or skin wounds. This is partially because of the risk from xenografts and allografts. Thus, the goal of this work was to study membranes of PVA and chitosan with and without crosslinking of genipin. The genipin was chosen as the crosslinking agent because it is a natural crosslinkerwhich has been showing promising in many studies for developing biomaterials. We examined the parameters to prepare the films and their physical and chemical characteristics, mechanical properties and their biocompatibility. The films produced in this study showed promising results for preparing biomaterial substitutes of epithelial tissue. The materials presented tensile strength compatible with the values of epithelial tissue and biocompatibility necessary for biomaterials.